Over the counter drugs: awareness and practice among the adults of Mushahar community - Mahato, Sanam; Bajracharya, Shanti (Journal of Chitwan Medical College, 2020)
Background: Over-the-counter drugs are the medicines that are sold without prescription of medical person. Though over-the-counter drugs are believed to be relatively safe, their inappropriate use could have serious implications. The aim of the study was to assess the awareness and practice on over-the-counter drugs among the Mushahar adults of Nawalparasi district, Nepal. Methods: A descriptive cross-sectional study was conducted among 102 respondents. Non-probability purposive sampling technique was used to select the sample using semi-structured questionnaire. Data was collected through face to face exit interview. Descriptive statistics and inferential statistics were used for analyzing the data. Results: Majority (91.2%) of the respondents knew that over-the-counter drugs are the unprescribed drugs by medical person and majority (95.1%) of the respondents used in case of fever and 83.3% of the respondents used because of easy accessibility More than half (52.9%) of the respondents had practiced over-the-counter drugs at least once within the first six months of data collection. The most preferred over-the-counter drugs were analgesics i.e 44.4%. On analyzing, there found a strong association between awareness level on demographic variables of educational status and occupation with the consumption of over-the-counter drugs as p value was <0.05. Conclusions: Study revealed that people use over-the-counter drugs because of easily availability and the most commonly used drugs were analgesics. So, different awareness programmes to the community and timely monitoring and intervention from the government is needed to prevent the rampant of over the counter drugs.